The tell-tale accent: Identification of regionally marked speech in German telephone conversations by forensic phoneticians - Köster, Olaf; Kehrein, Roland; Masthoff, Karen; Boubaker, Yasmin Hadj (International Journal of Speech, Language and the Law, 2012)
One of the most significant features in forensic phonetics used to identify a speaker is his or her so-called regional accent. In a speaker profiling task, German experts for voice comparison were evaluated concerning their performance and their methodological approach in accent identification. As a result, the experts as a group performed well; only very few severe confusions of regional accents occurred. Results also showed that the experts applied different strategies in identifying a speaker´s regional accent; the different methods were (a) aural-perceptual analysis, (b) acoustic analysis, (c) consultation of audio databases, and (d) consultation of literature on dialects. Participants also differed considerably in the amount of time they needed to complete the task.The most important finding is that no correlations existed between the performance (i.e. error rate) of the participants and (a) the time spent, (b) the number of methods applied, (c) the kind of method applied or (d) the perceived degree of difficulty. This leads to the conclusion that the performance in dialect identification may predominantly depend on the individual (innate or trained) skills of the expert in speaker identification.